Experience of 2nd line therapy with eltrombopag in patients with immune thrombocytopenia - S. G. Zakharov; T. A. Mitina; R. V. Vardanyan; Z. R. Tekeeva; I. N. Kontievskiy; Yu. Yu. Chuksina; A. V. Zakharova (Онкогематология)
Background. Immune thrombocytopenia (ITP), or idiopathic thrombocytopenic purpura, is a hematological autoimmune disease characterized by bleeding and an isolated decrease in platelet count <100 × 109 / l. The decision to start treatment for ITP depends on several factors. The ITP treatment strategy is based on the clinical symptoms, with a focus on reducing the risk of severe bleeding and increasing platelet counts.   Aim. To evaluate the efficacy of 2nd line therapy with the thrombopoietin receptor agonist eltrombopag in patients with ITP.   Materials and methods. 490 patients with ITP are under observation at the center for orphan diseases of M. F. Vladimirskiy Moscow Regional Research Clinical Institute. The present study included 186 patients with primary ITP after 1st line glucocorticosteroid therapy. eltrombopag, a thrombopoietin receptor agonist, was prescribed as the 2nd line of therapy.   Results. The median platelet count prior to eltrombopag therapy in all patients was 27.5 × 109 / l. after eltrombopag therapy, a significant (by 490 %) increase in platelet levels (median 135 × 109 / l) and a complete response according to clinical recommendations were noted.   Conclusion. Glucocorticosteroids (prednisolone, dexamethasone) remain the drugs of choice for the 1st line of therapy. Treatment with drugs of this group in most cases allows achieving an optimal platelet level and preventing bleeding. In case of inefficiency, intolerance, occurrence of side effects, the appointment of thrombopoietin receptor agonists eltrombopag or romiplostim is recommended. therapy with eltrombopag at a dose of 50 mg daily for several weeks has been able to achieve an increase in platelet levels, correct hemorrhagic syndrome, reduce the number of side effects during first-line glucocorticosteroid therapy, and improve the patient’s quality of life.